THE EFFECTIVENESS OF THE DECOCTION OF RED BETEL LEAVES (PIPER CROCANTUM) AGAINST THE REDUCED SYMPTOMS OF FLUOR ALBUS IN ADOLESCENT GIRLS - Purwanti, Rosa; Prihartanti, Niken Grah; Lestari, Rini Hayu (Journal of Vocational Health Studies, 2022)
Background: Fluor albus is excessive fluid from vagina that is not menstruation. To reduce the symptoms of fluor albus, non-pharmacological treatment from the decoction water of red betel leaves (Piper crocantum) was used in the present study. These red betel leaves (Piper crocantum) contain alkaloids that the green betel leaves do not have, and the alkaloids play a role as an antimicrobial agent. Besides, the red betel leaves have antiseptic power that is twice higher than the green betel leaves. The red betel leaves (Piper crocantum) also contain carvakrol which is anti-fungal and disinfectant, and it that can be used as an antiseptic medicine to maintain oral cavity health, cure fluor albus disease, and alleviate bad odor. Purpose: The present study aims to discover the effectiveness of the decoction of red betel leaves in reducing the fluor albus symptoms. Method: This study uses quasi-experimental research design with one group undertaking pre- and post-tests. It involved 20 adolescent girls of Al-Adzkia Sentul Boarding School in which the sample was taken using purposive sampling techniques. Further, a closed ended questionnaire is used to collect data, then analyzed using paired t-test. Result: The results showed a meaningful difference before being given treatment for 13.40. After treatment the value became 8.27 with a p-value < of α (0.005). Conclusion: The results this study indicated a decrease in symptoms of vaginal discharge after the use of red betel leaf decoction and recommended it to be used as a form of non-pharmacological therapy or traditional medicine in reducing fluor albus symptoms in adolescent girls.